Influence of Using Simplified Methods of Temperature in the Stud Connection Resistance - Yisel Larrua Pardo (Revista Cubana de Ingeniería, 2016)
In this paper, the impact that the use of simplified methods of determining temperatures evolution can produce in the stud connection resistance at elevated temperatures, in protected and unprotected composite beams, is evaluated. For this, comparisons between the obtained resistance when the temperatureis determined in the steel beam by simplifi ed methods and when it is obtained by finite elements method are carried out. It can be demonstrated that when the temperature is determined by the simplified method and the upper flange of the profi le presents a high section factor, it is overestimated in greatmeasure the resistance of the connection. This becomes more marked when in the design expressions the failure of the steel prevails.